Evaluation of Noise Pollution Levels in Hospitals and its Effects on Staff Health in AL - Najaf City in Iraq - Ahmed Abdel Hamid A. Hamoud1, Zaid Makki Mohammed H. AL-Hakkak1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of the study was to determine levels and sources of noise pollution in the hospitals and its effects on staff health in AL - Najaf city in Iraq. The study included measure sound levels in all wards in three hospitals (Al-sadr teaching hospital, Al-hakeem general hospital and Al-zahraa’ teaching hospital) using a digital sound level meter. The present work also examined distribution of symptoms caused by noise in employees of three hospitals and main sources of noise in hospitals by using prepared questionnaire through direct interview in the workplace. The results showed that the average measured A-weighted equivalent continuous level (LAeq) in all hospitals and in different shifts was more than recommended level (20 – 35 dB) of World Health Organization (WHO).The study revealed that the main sources of noise in inside the wards rooms of hospitals Al-Sadr Teaching Hospital, Al-Hakeem General Hospital and Al-Zahraa’ Teaching hospital were “staff conversation” (91%); “maneuver-patient treatment” (83%); “doors opening or closing” (77.5%); “mobile phone ringing and conversation” (76.5%).Moreover, it was observed that (32%) of respondents were headache by noise in hospitals . Moreover, the type of noise health effects that most complained among employees were vocal fatigue (31%), dizziness (30.5%), and feeling sick at the end of the workday (28.5%). This study concluded that the noise level in three hospitals was higher than the WHO rating; therefore, this problem causes raising the noise annoyance on of hospital staff.